Konstruksi Multicultural-Oriented Sejak Dini Melalui Keterampilan Menyimak Berbasis Al-Qur’an - Jannah, Rina Roudhotul (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2017)
This research is intended to reveal the importance of constructing of early multicultural-oriented education by linking it to the perspective of the Qur'an’s explain that listening activities affect the way of interpretation of one's socio-cultural outlook in solving problems such as SARA based conflict issues that often occur in Indonesia. The results showed that introducing multicultural through listening activities in early childhood can be done with the help of educators and parents. Some of these alternatives are the provision of learning models that have high intensity in children listening activities, nationalist revitalization that leads to national integration, nationalism that respects cultural differences, and include the soul of nationalism on the pre-school’s curriculum.